Rancang Bangun Mesin Pencacah Nangka Muda Sebagai Bahan Produksi Makanan Megono - Subekhi, TB.; Heryana, Ghany; Rajab, Dede Ardi; Nizarudin (Journal of Applied Mechanical Technology, 2023)
ABSTRACT - Megono is a typical food from the city of Pekalongan, the basic ingredients of megono are young jackfruit which is chopped into small pieces and various spices, the process of chopping young jackfruit manually is inefficient and unsafe. The purpose of this design is to produce an efficient and safe young jackfruit chopping machine, so that it can assist megono industry players in increasing megono production. The stages in designing a young jackfruit counter machine are: identifying problems, formulating problems by conducting literature studies and field studies, creating design concepts, establishing designs, assembling components, conducting machine testing and conducting analysis as a basis for making conclusions. The young jackfruit chopping machine has dimensions of 600 mm x 470 mm x 500 mm, uses an electric motor with a power of ½ HP, a voltage of 220 V and a rotation of 1400 rpm, the chopping shaft is made of ST60 material with a diameter of 20 mm, the knife used is made of AISI 5160 steel with dimensions of 100 mm x 50 mm x 4 mm. The capacity of the young jackfruit chopper is 96.58 kg/hour.